Advanced Nanoparticle Coatings for Stabilizing Layered Ni‐Rich Oxide Cathodes in Solid‐State Batteries (Adv. Funct. Mater. 23/2022). (3rd June 2022) - Ma, Yuan; Teo, Jun Hao; Walther, Felix; Ma, Yanjiao; Zhang, Ruizhuo; Mazilkin, Andrey; Tang, Yushu; Goonetilleke, Damian; Janek, Jürgen; Bianchini, Matteo; Brezesinski, Torsten
Abstract : Nanoparticle Protective Coatings In article number 2111829, Yuan Ma, Jürgen Janek, Torsten Brezesinski, and co‐workers propose a new coating strategy for layered Ni‐rich oxide cathode materials employing preformed (non‐agglomerated) nanoparticles dispersed in a liquid solvent. This approach leads to much improved cycling performance and stability and holds promise for application in solid‐ and liquid‐electrolyte based batteries.